Towards a Modern and Sustainable Sediment Management Plan in Mountain Catchment - Alessio Cislaghi; Emanuele Morlotti; Vito Giuseppe Sacchetti; Dario Bellingeri; Gian Battista Bischetti (GeoHazards, 2024)
Sediment management is fundamental for managing mountain watercourses and their upslope catchment. A multidisciplinary approach—not limited to the discipline of hydraulics—is necessary for investigating the alterations in sediment transport along the watercourse by detecting those reaches dominated by erosion and deposition processes, by quantifying the sediment volume change, by assessing the functionality of the existing torrent control structures, and by delimitating the riparian vegetation patches. To pursue these goals, specific continuous monitoring is essential, despite being extremely rare in mountain catchments. The present study proposed an integrated approach to determine the hydro-morphological–sedimentological–ecological state of a mountain watercourse though field- and desk-based analyses. Such an integral approach includes a rainfall–runoff model, a morphological change analysis and the application of empirical formulations for estimating peak discharge, mobilizable sediment/large wood volume and watercourse hydraulic capacity, at reach and catchment scales. The procedure was tested on the Upper Adda River catchment (North Italy). The results identified where and with what priority maintenance and monitoring activities must be carried out, considering sediment regime, torrent control structures and vegetation. This study is an example of how it is possible to enhance all existing information through successive qualitative and quantitative approximations and to concentrate new resources (human and economic) on specific gaps, for drafting a scientifically robust and practical sediment management plan.